BF3 bonded nano Fe3O4 (BF3/MNPs): an efficient magnetically recyclable catalyst for the synthesis of 1, 4-dihydropyrano[2, 3-c]pyrazole derivatives1. Issue 91 (9th October 2015) - Abdollahi-Alibeik, Mohammad; Moaddeli, Ali; Masoomi, Kianoosh
<x xml:space="preserve">Abstract</x> 1, 4-Dihydropyrano[2, 3-c]pyrazole derivatives were efficiently synthesized in a simple one-pot three-component reaction of various aldehydes with malononitrile and a 2-pyrazoline-5-one in the presence of BF3/MNPs as a novel nanostructured, heterogeneous and reusable catalyst.